The Healthy Eating Project: an experience report on food and nutritional education in a school on Cotijuba Island, PA, Brazil (Research, Society and Development, 2023)
Healthy eating is fundamental for the integral development of the individual, however, access to information about food can often be a difficulty in creating healthier habits. We report the experience of an educational practice in the 'Healthy Eating' project in a school on Cotijuba Island, PA, with the aim of strengthening learning from the perspective of nutritional education and building healthier and more sustainable eating habits. Participant observation was used to conduct the ludic-didactic activities developed as: didactic sequences, storytelling, conversation circles, dynamics involving eating and health habits, as well as the preparation of a meal with the help of all project participants. Themes related to Food and Nutrition Education were discussed in the classroom to highlight the functions of food nutrients in the human body and present the different nutrients present in the different types of food to students, helping them to understand the importance of a more balanced and healthy diet. The experience of this practice allowed the development of a process of reflection of the reality observed among the participating students and contributes to the propagation of these habits inside and outside the school community.